Laryngeal amyloidosis: diagnosis, pathophysiology and management. (30th May 2017) - Phillips, N M; Matthews, E; Altmann, C; Agnew, J; Burns, H
Abstract: Background: Laryngeal amyloidosis represents approximately 1 per cent of all benign laryngeal lesions, and can cause variable symptoms depending on anatomical location and size. Treatment ranges from observation through to endoscopic microsurgery, laser excision and laryngectomy. Objectives: To highlight the diversity of presentations, increase awareness of paediatric amyloidosis and update the reader on current management. Case series: Five cases are illustrated. Four adult patients were female, and the one child, the second youngest in the literature, was male. Amyloid deposits were identified in all laryngeal areas, including the supraglottis, glottis and subglottis. Treatment consisted of balloon dilatation, endoscopic excision, laser cruciate incision, and resection with carbon dioxide laser, a microdebrider and coblation wands. Conclusion: Laryngeal amyloidosis remains a rare and clinically challenging condition. Diagnosis should be considered for unusual appearing submucosal laryngeal lesions. Treatment of this disease needs to be evaluated on a case-by-case basis and managed within an appropriate multidisciplinary team.